Targeted Analysis of Mitochondrial Protein Conformations and Interactions by Endogenous ROS‐Triggered Cross‐Linker Release - Wen Zhou; Yuwan Chen; Wenxin Fu; Xinwei Li; Yufei Xia; Qun Zhao; Baofeng Zhao; Yukui Zhang; Kaiguang Yang; Lihua Zhang (Advanced Science)
Abstract The study of in situ conformations and interactions of mitochondrial proteins plays a crucial role in understanding their biological functions. Current chemical cross‐linking mass spectrometry (CX‐MS) has difficulty in achieving in‐depth analysis of mitochondrial proteins for cells without genetic modification. Herein, this work develops the reactive oxygen species (ROS)‐responsive cross‐linker delivery nanoparticles (R‐CDNP) targeting mitochondria. R‐CDNP contains mitochondria‐targeting module triphenylphosphine, ROS‐responsive module thioketal, loading module poly(lactic‐co‐glycolic acid) (PLGA), and polyethylene glycol (PEG), and cross‐linker module disuccinimidyl suberate (DSS). After targeting mitochondria, ROS‐triggered cross‐linker release improves the cross‐linking coverage of mitochondria in situ. In total, this work identifies 2103 cross‐linked sites of 572 mitochondrial proteins in HepG2 cells. 1718 intra‐links reveal dynamic conformations involving chaperones with ATP‐dependent conformation cycles, and 385 inter‐links reveal dynamic interactions involving OXPHOS complexes and 27 pairs of possible potential interactions. These results signify that R‐CDNP can achieve dynamic conformation and interaction analysis of mitochondrial proteins in living cells, thereby contributing to a better understanding of their biological functions.